Effects of tutin and its derivatives on GAD and GABA-T in Pseudelatia separata (Lepidoptera: Noctuidae) - DU, WEIWEI; NAN, XIAONING; LI, MENGLOU (Revista Colombiana de Entomología, 2012)
Tutin inhibits the receptors of the neurotransmitter γ-aminobutyric acid (GABA). In this work, we compared tutin with its derivatives, 2-(4-methoxybenzoyloxy)-tutin (T1), 2-(3,5-dinitrobenzoyloxy)-tutin (T2), 2-(6-chloronicotinoyloxy)-tutin (T3), and 2-(4-nitrobenzoyloxy)-tutin (T4), in terms of their effects on feeding and the feedback regulation mechanism of GABA metabolism. Spectrophotometry was used to determine the glutamic acid decarboxylase (GAD) and γ-aminobutyric acid transaminase (GABA-T) activities of these compounds in 3rd instar larvae of Pseudelatia separata. Clear antifeedant activities were manifested by T1 and especially T3, whereas T4 stimulated feeding in P. separata. GAD and GABA-T activities in larvae treated with all five toxins differed significantly from the control and from one other (P < 0.05) in terms of treatment types and exposure times. The effects of the toxins on GAD and GABA-T were time-dependent for 48 h. GAD activities were inhibited by tutin, T2, T3, and T4, and were enhanced by T1. GABA-T activities were increased by all the toxins in varying degrees. Variation of GABA content in P. separata larvae resulted from the disturbance of GAD and GABA-T by tutin and its derivatives. Results suggest that T3, with its nicotinoyl group, is the most promising novel active ingredient for pest control.